Green Computing : Efficient Practices And Applications - Sen, Deepanjan; Chowdhury, Dilip Roy (International Journal of Computer Sciences and Engineering, 2025)
Today the importance of going green have been realized both in terms of environmental issues and cost minimization by implementing different strategies and policies by the ICT industry. Going green suggest the environmentally responsible practice of computers and related resources of ICT. For a sustainable environment, today Green Computing is an emerging topic, because of efficient power usage, minimal or no emission of carbon footprint, also proper disposal of electronic waste (e-waste) and many more, thus to take less participation in the global warming phenomenon. In this study, emphasis has given ondiminishing the energy and carbon footprint of computer and its related resources like- monitors, printers using green computing.